Health conferences: metasynthesis of good practices, obstacles and recommendations based on experiences in Brazil, 1986-2016 - Ricardi, Luciani Martins; Shimizu, Helena Eri; Santos, Leonor Maria Pacheco (Saúde e Sociedade, 2020)
This study sought to identify the evidence produced on Brazilian health conferences and to systematize good practices, obstacles and recommendations to qualify social participation in the Unified Health System. The methodology used was literature review with metasynthesis of studies published from 1986 to 2016 from the BIREME and Pubmed databases. It resulted in 507 articles, of which 15 met the criteria of primary qualitative studies on Brazilian health conferences. Most articles are experience reports of municipal scope published in the last ten years. The metasynthesis allowed to systematize the results into improvements, obstacles and recommendations for the conferences according to different axes: role, dissemination, participation, organization and referrals. Despite the importance of these conferences to the democratization of the health system, we observed that access and participation need to be qualified, be promoted, include population feedback, empowerment, political formation and articulation with other areas for debate. The most notable recommendations were the proposals for dealing with the obstacles presented, more specifically the need to monitor, improve the articulation with the health councils, and the greater influence of Conference resolutions on public management.